INFLUENCE OF DEPOSITION TEMPERATURE ON THE CORROSION RESISTANCE OF ELECTRODEPOSITED ZINC-NICKEL ALLOY COATINGS - MOHAN, GOPI NATH NAMBIAR (IRC, 2017)
Carbon steel, a metal used in various industrial applications as its functions and properties are apt and compatible with industrial functions are extremely prone to corrosion. Zinc and its alloys can be coated to provide corrosion protection to carbon steel and out of which, zinc-nickel alloy have been identified as the potential candidate as it possesses the highest corrosion resistance when compared with zinc in pure form. Deposition parameters play an important role in the microstructure, elemental composition and corrosion resistance property of zinc-nickel alloy. This paper focuses on the zinc-nickel alloy coatings which were electrodeposited on carbon steel from chloride bath using the technique of chronopotentiometry at different temperatures. The elemental composition and surface morphology analysis of zinc-nickel coated samples were done using SEM coupled with EDX.